Land Subsidence: The Presence of Well and Clay Layer in Aquifer - Budihardjo, Mochamad Arief; Chegenizadeh, Amin; Nikraz, Hamid (AENSI Publisher, 2014)
Background: In general, the aquifer may contain a combination of different soil types. Response of the aquifer toward the changes of ground water level due to groundwater extraction depends on the characteristics of the soil constituent in the aquifer. Moreover, aquifer containing a combination of grain and fine soil, such as sand and clay which are completely different in the permeability coefficient, tends to react differently due to any change of the groundwater level. Objective: This paper aims to investigate land subsidence due to pumping. As part of this research, different clay zone thicknesses and types (i.e. continues and non-continues) were evaluated and examined. Wells were also inserted in different locations in the clay zone, a discharge rate applied at rate of 20m3/day and land subsidence measured. In this article, the difference of surface layer deformation response of some sand aquifers containing clay were investigated by using a finite element model. Several scenarios of aquifers alteration, such as the size of the clay layer, number of clay zone, variations in groundwater levels, location and number of wells and also changing of the groundwater levels were analysed using Plaxis 2D (a finite element software). In the simulation, groundwater discharge was determined at 20 m3/day and pumping time was prescribed for 5 years. Results: The results indicate that groundwater changes will trigger surface deformation in each simulated aquifer. However, the deformation of the ground surface in each aquifer is varies. It is obvious that the presence of clay layer in the aquifer influence the response of soil surface deformation after the groundwater was pumped for 5 years. The location and the number of wells also affect the degree of deformation of the ground surface. The thickness of clay layer and the number of clay zone also contribute on the change of the surface aquifer shape. Conclusion: It can be expected that the surface of the ground surface around the well sagging much more than the surrounding areas, the aquifer contains low- permeability layers underneath. Considering its effect on municipal areas, land subsidence resulting from excessive groundwater withdrawal must become an integral part of the urban planning process to achieve sustainable planning.